Per-oral endoscopic myotomy for achalasia cardia: outcomes in over 400 consecutive patients - Nabi, Zaheer; Ramchandani, Mohan; Chavan, Radhika; Kalapala, Rakesh; Darisetty, Santosh; Rao, Guduru Venkat; Reddy, Nageshwar (Endoscopy International Open, 2017)
Background and study aims Per-oral endoscopic myotomy (POEM) has emerged as an efficacious treatment modality for the management of achalasia cardia (AC) and non-achalasia spastic esophageal motility disorders. Initial results are encouraging. We analyzed the safety and efficacy of POEM in a large cohort of patients with AC.Patients and methods The data from patients who underwent POEM (from January 2013 to June 2016) was prospectively collected and analyzed. Clinical success was defined as Eckardt score ≤ 3 after POEM procedure. Objective parameters including high-resolution manometry (HRM) and timed barium swallow (TBS) were analyzed and compared before and after the procedure. Gastroesophageal reflux was analyzed using 24-hour pH impedance study and esophagogastro-duodenoscopy. Results A total of 408 patients (mean age 40 years, range 4 – 77 years) underwent POEM during the specified period. POEM could be successfully completed in 396 (97 %) patients. Clinical success rates at 1, 2 and 3 years were 94 %, 91 % and 90 %, respectively. Mean Eckardt score was 7.07 ± 1.6 prior to POEM and 1.27 ± 1.06 after POEM (P = 0.001) at 1 year. Significant improvement in esophageal emptying on TBE (> 50 %) was documented in 93.8 % patients who completed 1-year follow up. Pre-procedure and post-procedure mean lower esophageal sphincter pressure was 45 ± 16.5 mmHg and 15.6 ± 6.1 mmHg, respectively (P = 0.001). Technical and clinical success were comparable in naïve vs prior treated cases (97.3 % vs 96.8 %, P = 0.795) (95.7 % vs 92.6 %, P = 0.275). GERD was documented in 28.3 % patients with 24-hour pH-impedance study and erosive esophagitis was seen in 18.5 % of patients who underwent POEM. Conclusions POEM is safe, effective and has a durable response in patients with achalasia cardia. Prior treatment does not influence the outcomes of POEM.